2021
DOI: 10.1155/2021/9932425
|View full text |Cite
|
Sign up to set email alerts
|

The Many Faces of Purpura: Vancomycin-Induced Leukocytoclastic Vasculitis

Abstract: Leukocytoclastic vasculitis is a rare form of immune-mediated vasculitis that might be caused by infections or autoimmune diseases or might be precipitated by specific medications. We describe a 65-year-old patient, who was receiving vancomycin for a methicillin-sensitive Staphylococcus aureus permacath infection. Vancomycin was chosen due to medication non-adherence and the patient’s desire to receive antimicrobial therapy in conjunction with his scheduled dialysis sessions. The patient’s medical history was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In our case, vancomycin was used for 6 weeks before it was de‐escalated to SMT. Vancomycin can also cause LCV, as evidenced by published reports 14–16 . However, in our patient, the rash appeared after 3 days of initiation of SMT.…”
Section: Discussionmentioning
confidence: 41%
“…In our case, vancomycin was used for 6 weeks before it was de‐escalated to SMT. Vancomycin can also cause LCV, as evidenced by published reports 14–16 . However, in our patient, the rash appeared after 3 days of initiation of SMT.…”
Section: Discussionmentioning
confidence: 41%
“…The most common clinical finding of LCV is the presence of a cutaneous non-blanching palpable purpura, although exclusive erythema, maculopapular lesions, or petechiae have also been noted in the literature [ 2 - 3 ]. Histological analysis of the cutaneous lesions in LCV typically shows sub-epidermal acantholysis with a dense inflammatory infiltrate predominantly composed of neutrophils, leading to a subsequent release of lysosomal enzymes causing a fibrinoid necrosis of the vasculature [ 4 - 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 60 published articles were included, comprising a total of 74 cases published between 1955 and 2021 (Table 1). 20,26,27,30 86 Analyses of the reported cases of antibiotic-induced leukocytoclastic vasculitis revealed that it is associated with numerous classes of antibiotic, including penicillin (amoxicillin, amoxicillin-clavulanic acid, oxacillin), cephalosporins (cefazolin, cephalexin, cefuroxime, ceftriaxone, cefotaxime), fluoroquinolone (ciprofloxacin, levofloxacin, ofloxacin), macrolides (azithromycin, clarithromycin), vancomycin, teicoplanin, trimethoprim-sulfamethoxazole, dapsone, linezolid, pristinamycin, tigecycline, isoniazid, streptomycin, rifampin, ethambutol, and pyrazinamide.…”
Section: Discussionmentioning
confidence: 99%